Does Foreign Ownership Restrict Earnings Management? The Case of China - Sang Ho Kim,; Yohan An,; Prabhu Udawatte, (Asian Academy of Management Journal of Accounting and Finance, 2020)
This study examines the effects of foreign ownership on Chinese firms’ earnings management practices. Given that foreign shareholders are expected to increase the transparency of the firm’s management, this study anticipates that foreign ownership would restrict earnings management of both the accrual-based earnings management (AEM), and real activity- based earnings management (REM). Using the panel dataset of the B-share and H-share firms from 2003 to 2015, this study finds that the H-share firms which cross-listed on both the mainland China and Hong Kong Stock Exchanges are more likely to manage earnings through the discretionary accruals as well as the changes in the firms’ operations. In contrast the B-share firms are less likely to manage earnings by using the discretionary accruals. This study also finds that state control and large shareholdings of foreigners can restrict the B-share firms’ earnings management through the discretionary accruals. The findings noted in this study imply that foreign investors who want to invest in Chinese firms must be more cautious about market inefficiency and the information asymmetry problem in the Chinese stock markets.